THE ROLE OF INDEPENDENT COMMISIONER, INSTITUTIONAL OWNERSHIP, AND INTELLECTUCAL CAPITAL IN BANKING CORPORATE VALUE - Sari Yunita; Ignatius Roni Setyawan (International Journal of Application on Economics and Business, 2025)
This study seeks to empirically analyze the effect of Board Independence, Institutional Ownership, and Intellectual Capital on Corporate Value in the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study is motivated by the increasing need for banks to enhance their corporate value in order to stay competitive in an era marked by intense industry competition and rapid technological advancements. Inconsistencies in previous research findings regarding the factors that influence corporate value also highlight the need for further investigation. The study population includes all banking companies listed on the IDX between 2021 and 2023. Using purposive sampling, 26 banks were selected, yielding a total of 312 observations over the three-year span. Data analysis was conducted using multiple linear regression with the help of E-Views version 12. The findings indicate that Board Independence has a significant positive influence on Corporate Value. Institutional Ownership, however, does not have a statistically significant effect, while Intellectual Capital shows a significant negative impact on Corporate Value